2021
DOI: 10.1007/s00122-021-03922-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the genetic control of seed coat color in a RIL population of common bean (Phaseolus vulgaris L.)

Abstract: Key message Three genes associated with the seed coat color in a TU/Musica RIL population were located on a genetic map, and two candidate genes proposed to control black seed coat in the TU genotype were characterized. Abstract Seed coat color is an important characteristic of common bean (Phaseolus vulgaris L.) associated with the marketability of dry bean cultivars, quality and nutritional characteristics of seed, as well as response to pathogens. In this study, the genetic control of seed coat color in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…Here, we describe biochemical analysis of introgression lines, with a shared background and different recessive v alleles, and found that dihydromyricetin-related compounds, including delphinidin, were greatly reduced in seeds and flowers with recessive v alleles. We physically mapped V near a F3′5′H gene model, a result also reported recently using RIL mapping by García-Fernández et al (2021) . Our sequencing of natural variants and a haplotype reconstruction conclusively shows that V indeed encodes F3′5′H.…”
Section: Introductionsupporting
confidence: 54%
“…Here, we describe biochemical analysis of introgression lines, with a shared background and different recessive v alleles, and found that dihydromyricetin-related compounds, including delphinidin, were greatly reduced in seeds and flowers with recessive v alleles. We physically mapped V near a F3′5′H gene model, a result also reported recently using RIL mapping by García-Fernández et al (2021) . Our sequencing of natural variants and a haplotype reconstruction conclusively shows that V indeed encodes F3′5′H.…”
Section: Introductionsupporting
confidence: 54%
“…These regulatory genes include a MYB transcription factor that forms part of the MBW (MYB-βHLH-WD40) ternary complex, which activates the late biosynthetic proteins required for the anthocyanin and proanthocyanidin synthesis in other species [ 41 ]. One of these genes encoding a MYB113- related factor, Phvul.008G038400 , has been proposed as a gene responsible for the black seed coat color expression in the cultivar TU [ 26 ]. Another wide QTL for phenolic metabolites, Phe_Pv08(62.5), was located at the end position of chromosome Pv08, between 62.58–63.28 Mbp, associated with the synthesis of the anthocyanin Pel_G.…”
Section: Discussionmentioning
confidence: 99%
“…The other QTL including the black_NB seed trait, C_Pv06(4.2), corresponds with the V color gene. The gene Phvul.006G018800 located in this region encodes a F3’,5’H and was previously proposed as the gene controlling the black seed coat color in the cultivar TU [ 26 ]. Later, McClean et al [ 27 ] confirmed that V encodes an F3’,5’H required for the expression of dihydromyricetin-derived metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations